Analysis of Main Account Versus Second Account Instagram as A Media for Self-Disclosure of Generation Z in Baubau City - Zayana,; Muhammad Hidayatullah,; Muhammad Rizal Ardiansyah Putra, (Mediakita, 2025)
This study analyzes the differences in main account and second account Instagram uploads as a medium for self-disclosure among Gen Z students in Baubau city, and how the process of selecting information is carried out before being uploaded to each account. This research employs a descriptive qualitative approach to understand social events or symptoms, focusing on the overall picture of the research subject. The results of this study indicate that there are differences in uploads on the main account and secondary account of Instagram, considering various factors such as audience, level of trust, type of content, purpose, and socio-cultural aspects. Thus, it is not uncommon for informants to use private accounts and close friend features on their Instagram accounts. This process illustrates how informants have differentiated between the front stage and the back stage, specifically identifying which aspects of private life and which aspects of public life to balance and manage in terms of self-disclosure, privacy, and image.